Preparation method of aluminum adsorbent of aluminum-magnesium solid solution
During the lithium resource extraction process, the aluminum-based adsorbent precursor of aluminum-magnesium solid solution is used to improve the adsorption performance through co-precipitation method and intercalation method, and the existing problem of low adsorption performance is solved, and efficient lithium resource extraction and environmentally friendly processes are achieved.
Patent Information
- Application Number
- CN202411861810.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
During the existing lithium resource extraction process, the adsorption performance of aluminum-based adsorbents is relatively low and it is difficult to effectively improve.
By dissolving and mixing soluble aluminum salt, lithium salt and magnesium salt, and adjusting the pH value using alkali solution, an aluminum-based adsorbent precursor for aluminum-magnesium solid solution is prepared, and the adsorption performance is improved through co-precipitation method and intercalation method.
It improves the adsorption capacity and stability of aluminum-based adsorbents, takes into account the concept of green and environmental protection, and achieves the improvement of high lithium embedding rate and pure water elution lithium ion rate.
Smart Images

Figure CN119771342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium extraction from salt lake chemicals, and in particular to a method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution. Background Art
[0002] As an efficient and clean energy storage device, lithium-ion batteries are widely used in electric vehicles, electronic equipment and other fields. Among the many lithium extraction methods, although the extraction method has a certain extraction efficiency, it has problems such as large consumption of organic solvents and easy environmental pollution; the calcination method has high energy consumption and strict requirements on equipment; the electrodialysis method has high costs and complex operations. In contrast, the adsorption method stands out with its unique advantages. The adsorption method is generally believed to be able to achieve high selectivity, short cycle and effective lithium extraction in high magnesium-to-lithium ratio brine systems. Through the adsorption method, liquid lithium resources can be effectively separated and extracted, providing a stable lithium source guarantee for the sustainable development of the lithium-ion battery industry.
[0003] Using layered aluminum adsorbents (LiAl-LDHs) to extract lithium in the adsorption method is a common method of lithium extraction. Layered aluminum adsorbents (LiAl-LDHs) are layered crystals composed of oxygen-coordinated octahedral layers. There are hydroxyl groups on the six vertices of the octahedron. Water molecules and anions are inserted between the lithium and aluminum layers to form a lithium extraction precursor, and then the aluminum adsorbent is obtained after lithium is eluted with water. This layered aluminum adsorbent is suitable for many salt lakes with high magnesium-lithium ratios and low grades. It has the advantages of green environmental protection and recycling. However, the adsorption performance of layered aluminum adsorbents (LiAl-LDHs) needs to be improved. Therefore, how to deeply explore and further improve the adsorption performance of aluminum adsorbents in the adsorption method has become a very challenging and urgent problem in the field of lithium resource extraction research. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution to solve the problem of low adsorption performance of aluminum-based adsorbents in the existing lithium resource extraction process.
[0005] A method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution, the preparation method comprising the following steps:
[0006] S1, dissolving a soluble aluminum salt, a soluble lithium salt and a soluble magnesium salt in deionized water to obtain a mixed salt solution;
[0007] S2, dissolving a soluble alkali in deionized water to obtain an alkali solution;
[0008] S3, adding the alkaline solution dropwise to the mixed salt solution, and adjusting the pH value of the mixed salt solution to prepare a mixture;
[0009] S4. Performing solid-liquid separation on the mixture to obtain a supernatant and a solid, and washing and drying the solid to obtain an aluminum-based adsorbent precursor powder.
[0010] Preferably, the soluble magnesium salt in step S1 is selected from one or both of anhydrous magnesium chloride and hydrated magnesium chloride.
[0011] Preferably, the soluble aluminum salt in step S1 is selected from one or more of anhydrous aluminum chloride, hydrated aluminum chloride, aluminum sulfate, hydrated aluminum sulfate, aluminum nitrate, hydrated aluminum nitrate, aluminum silicate and aluminum sulfide.
[0012] Preferably, the soluble lithium salt in step S1 is selected from one or more of anhydrous lithium chloride, hydrated lithium chloride, anhydrous lithium hydroxide, hydrated lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate.
[0013] Preferably, the soluble alkali in step S1 is selected from one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, ammonia water and urea.
[0014] Preferably, in step S1, the molar ratio of aluminum ions in the soluble aluminum salt, lithium ions in the soluble lithium salt and magnesium ions in the soluble magnesium salt is (0.1-1):(0.1-2):(0.1-2).
[0015] Preferably, in the mixed salt solution in step S1, the aluminum ion concentration is 0.1 mol / L to 10 mol / L, the lithium ion concentration is 0.1 mol / L to 10 mol / L, and the magnesium ion concentration is 0.1 mol / L to 10 mol / L.
[0016] Preferably, the concentration of the alkaline solution in step S2 is 0.5 mol / L to 5.0 mol / L.
[0017] Preferably, in step S3, the alkaline solution is dripped at 5 mL / min at 35°C to 50°C. -1 ~60mL·min -1 The mixed salt solution is dripped into the mixed salt solution at a speed, and the pH value of the mixed salt solution is adjusted to 6.0-8.0.
[0018] Preferably, the temperature for drying the solid obtained in step S4 is 40°C to 80°C.
[0019] The present invention provides a method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution, wherein a soluble aluminum salt, a soluble lithium salt and a soluble magnesium salt are dissolved and mixed, and the pH value of the mixed solution is adjusted using an alkaline solution, so that an aluminum-based adsorbent precursor powder of an aluminum-magnesium solid solution can be prepared. In the preparation process, a low-content magnesium salt is used to replace Al on a small part of the octahedral crystal vertices with Mg through a coprecipitation method and an intercalation method, and the charge is supplemented by the site where Li is close to Mg, and anions are inserted between the aluminum-based adsorbent layers to balance the charge and increase the adsorption capacity of the adsorbent while ensuring structural stability. Compared with other modified doping, such as doping with Fe, Zn, etc., there will be dissolution problems. When adsorbed in the salt lake, it is bound to enter the salt lake and pollute the quality of the salt lake brine, and the newly introduced metal will also affect the reuse of the brine. Mg is the most abundant metal element in brine, and the problem of dissolution can be ignored. Therefore, the aluminum-based adsorbent of the aluminum-magnesium solid solution in the present invention not only increases its adsorption capacity and stability, but also takes into account the concept of green environmental protection. It is an adsorbent that can replace conventional LDHs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A flow chart of the method for preparing the doped aluminum-based adsorbent provided by the present invention;
[0021] Figure 2 A comparison chart of the adsorption capacity of the adsorbents in Comparative Example 1 and Example 1 provided by the present invention;
[0022] Figure 3 The XRD spectrum of the adsorbent in Example 2 provided by the present invention;
[0023] Figure 4 This is the XRD spectrum of the adsorbent in Example 3 provided by the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of this application clearer, the present invention is further described below in conjunction with the accompanying drawings and embodiments, and the embodiments of the present invention include but are not limited to the following embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] In this embodiment, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0026] The terms "first" and "second" in the description and claims of this embodiment are used to distinguish different objects rather than to describe a specific order of objects. For example, a first target object and a second target object are used to distinguish different target objects rather than to describe a specific order of target objects.
[0027] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0028] In the description of the embodiments of the present application, unless otherwise specified, the meaning of "multiple" refers to two or more than two. For example, multiple processing units refer to two or more processing units; multiple systems refer to two or more systems.
[0029] Figure 1 The flowchart of the method for preparing the aluminum-based adsorbent of the aluminum-magnesium solid solution provided in the embodiment of the present invention is shown in FIG. Figure 1 , a method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution, the preparation method comprising the following steps:
[0030] S1. Dissolve a soluble aluminum salt, a soluble lithium salt and a soluble magnesium salt in deionized water to obtain a mixed salt solution.
[0031] In a preferred embodiment, the aluminum ion concentration in the mixed salt solution in step S1 is 0.1 mol / L to 10 mol / L, the lithium ion concentration is 0.1 mol / L to 10 mol / L, and the magnesium ion concentration is 0.1 mol / L to 10 mol / L.
[0032] In a preferred embodiment, the molar ratio of aluminum ions in the soluble aluminum salt, lithium ions in the soluble lithium salt and magnesium ions in the soluble magnesium salt in step S1 is (0.1-1):(0.1-2):(0.1-2).
[0033] Among them, when preparing the aluminum-based adsorbent of the aluminum-magnesium solid solution, the amount of soluble aluminum salt, soluble lithium salt and soluble magnesium salt is obtained according to the molar ratio of ions in the reaction process to ensure that the soluble aluminum salt, soluble lithium salt and soluble magnesium salt obtained meet the reaction requirements.
[0034] S2. Dissolve a soluble alkali in deionized water to obtain an alkali solution.
[0035] In a preferred embodiment, the concentration of the alkaline solution in step S2 is 0.5 mol / L to 5.0 mol / L.
[0036] S3, adding the alkaline solution dropwise into the mixed salt solution, and adjusting the pH value of the mixed salt solution to prepare a mixture.
[0037] In a preferred embodiment, in step S3, the alkaline solution is dripped at 5 mL / min at 35°C to 50°C. -1 ~60mL·min -1 The mixed salt solution is dripped into the mixed salt solution at a speed, and the pH value of the mixed salt solution is adjusted to 6.0-8.0.
[0038] S4, performing solid-liquid separation on the mixture to obtain a supernatant and a solid, and washing and drying the solid to obtain an aluminum-based adsorbent precursor powder.
[0039] In a preferred embodiment, the temperature for drying the solid obtained in step S4 is 40°C to 80°C.
[0040] In a specific implementation scheme, 16 mol / L concentrated nitric acid is used in the water washing stage to remove impurities in the preparation process. Since concentrated nitric acid will cause the aluminum-based adsorbent precursor powder to elute lithium ions (the first elution) in the preparation stage, it is necessary to measure the elution rate of lithium ions in the aluminum-based adsorbent precursor powder of the aluminum-magnesium solid solution. Then, verification is performed based on the intercalation rate and elution rate of lithium ions to obtain the desired aluminum-based adsorbent.
[0041] In a specific implementation scheme, the intercalation rate and elution rate of lithium ions were compared with the original adsorbent, and it was found that the intercalation rates of the two were the same, and the elution rate of lithium ions of the aluminum-based adsorbent of the aluminum-magnesium solid solution was 10% to 20% lower than that of the original adsorbent, proving that its structure is more stable and the binding force between ions is higher.
[0042] The chemical mechanism of the aluminum-based adsorbent of the aluminum-magnesium solid solution in the present invention is as follows:
[0043] First, when preparing layered aluminum adsorbents (LiAl-LDHs), the preparation process is carried out through a chemical mechanism:
[0044] For example, aluminum chloride, lithium chloride and sodium hydroxide are used as raw materials to obtain LiAl(OH)3·H2O according to the above mechanism, and LiAl(OH)3·H2O is further crystallized to form layered LiAl-LDHs.
[0045] When soluble magnesium salt is added, since the layered aluminum adsorbent (LiAl-LDHs) itself is a layered crystal composed of oxygen-coordinated octahedral layers stacked together, there are hydroxyl groups on the six vertices of the octahedron. After the lithium-aluminum layers are inserted with water molecules and anions, a lithium extraction precursor can be formed. Therefore, when Mg is added, Mg can replace the Al on a small number of octahedral crystal vertices with Mg, and the charge is completed by the site where Li is close to Mg. At the same time, anions are inserted between the aluminum-based adsorbent layers to balance the charge and increase the adsorption capacity of the adsorbent while ensuring structural stability.
[0046] In a preferred embodiment, the soluble magnesium salt in step S1 is selected from one or both of anhydrous magnesium chloride and hydrated magnesium chloride.
[0047] In a more preferred embodiment, the soluble magnesium salt is selected from anhydrous magnesium chloride.
[0048] In a preferred embodiment, the soluble aluminum salt in step S1 is selected from one or more of anhydrous aluminum chloride, hydrated aluminum chloride, aluminum sulfate, hydrated aluminum sulfate, aluminum nitrate, hydrated aluminum nitrate, aluminum silicate and aluminum sulfide.
[0049] In a more preferred embodiment, the soluble aluminum salt is selected from anhydrous aluminum chloride. When the soluble aluminum salt is selected from hydrated aluminum chloride, aluminum chloride hexahydrate can be selected.
[0050] In a preferred embodiment, the soluble lithium salt in step S1 is selected from one or more of anhydrous lithium chloride, hydrated lithium chloride, anhydrous lithium hydroxide, hydrated lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate.
[0051] In a more preferred embodiment, the soluble lithium salt is selected from anhydrous lithium chloride.
[0052] In a preferred embodiment, the soluble alkali in step S1 is selected from one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, ammonia water and urea.
[0053] In a more preferred embodiment, the soluble base is selected from sodium hydroxide.
[0054] Example 1
[0055] This embodiment 1 provides an aluminum-based adsorbent of an aluminum-magnesium solid solution, and the preparation method thereof is as follows:
[0056] (1) Selection of raw materials
[0057] Aluminum chloride hexahydrate, lithium chloride, magnesium chloride and sodium hydroxide are selected, wherein a certain amount of sodium hydroxide, aluminum chloride hexahydrate, lithium chloride and magnesium chloride are respectively weighed according to the molar ratio in the reaction process, so that the molar ratio of the elements Na:Al:Li:Mg is 3.3:7:5:3.
[0058] (2) Aluminum chloride hexahydrate, lithium chloride and magnesium chloride are dissolved in deionized water to obtain a mixed solution, wherein the aluminum ion concentration in the mixed solution is ensured to be 0.1 mol / L to 10 mol / L, the lithium ion concentration is 0.1 mol / L to 10 mol / L, and the magnesium ion concentration is 0.1 mol / L to 10 mol / L.
[0059] (3) Dissolve sodium hydroxide in deionized water to obtain a sodium hydroxide solution.
[0060] (4) adding sodium hydroxide solution dropwise to a mixed solution of aluminum chloride, lithium chloride and magnesium chloride at a uniform rate, controlling the pH of the reaction system to be 7.5, stirring at a constant temperature for 10 minutes and then standing, and then subjecting the obtained mixture to solid-liquid separation. During the solid-liquid separation, taking the lower layer of white precipitate, washing with water, centrifuging and drying, and then grinding to obtain an adsorbent precursor of an aluminum-magnesium solid solution.
[0061] Comparative Example 1
[0062] Comparative Example 1 provides a layered aluminum adsorbent (LiAl-LDHs). When preparing the layered aluminum adsorbent (LiAl-LDHs), Li + and Al 3+ The molar ratio is 1:2, and then the Li + and Al 3+ The mixed solution is added dropwise to a sodium hydroxide solution, and then the pH value is adjusted to: pH <9, and then dried to obtain the adsorbent Li / Al-LDHs.
[0063] The adsorbents in Example 1 and Comparative Example 1 were subjected to an adsorption capacity test for comparison. 0.5 g of the aluminum-based adsorbent precursor of the aluminum-magnesium solid solution in Example 1 was mixed with 100 ml of deionized water, and then oscillated and deintercalated on a constant temperature shaker for 2 hours, and then the aluminum-based adsorbent of the aluminum-magnesium solid solution obtained by oscillation and deintercalation was mixed with a solution having an initial lithium ion concentration of 400 ppm, and then oscillated and adsorbed on a constant temperature shaker for 3 hours. At the same time, 0.5 g of the precursor of the Li / Al-LDHs adsorbent was mixed with 100 ml of deionized water, and then oscillated and deintercalated on a constant temperature shaker for 2 hours to obtain a Li / Al-LDHs adsorbent, and then the Li / Al-LDHs adsorbent obtained by oscillation and deintercalation was mixed with a solution having an initial lithium ion concentration of 400 ppm, and then oscillated and adsorbed on a constant temperature shaker for 3 hours.
[0064] Among them, since the adsorbent precursor of the aluminum-magnesium solid solution prepared in Example 1 contains lithium ions, the lithium ions added in the synthesis stage need to be removed before the first use. Therefore, when measuring the adsorption amount of the adsorbent, the adsorbent precursor of the aluminum-magnesium solid solution of the adsorbent needs to be eluted for the second time. The second elution is carried out in the form of oscillation deintercalation. Similarly, the adsorbent precursor prepared in Comparative Example 1 also needs to be eluted for the second time.
[0065] Figure 2 The adsorption capacity comparison diagram of the adsorbent in Comparative Example 1 and Example 1 provided by the present invention is shown in FIG. Figure 2 It can be seen that the adsorption saturation time of the Mg-LDHs-Cl adsorbent in Example 1 is less than 30 min, and the adsorption capacity can be greater than 8 mg / g. The adsorption capacity of the Li / Al-LDHs adsorbent in Comparative Example 1 is less than 8 mg / g. Figure 2 It can be seen that the adsorption capacity of the Mg-LDHs-Cl adsorbent is greater than that of the Li / Al-LDHs adsorbent. This indicates that in the second elution stage, the structure of the Mg-LDHs-Cl adsorbent is more stable, and the structure of the Li / Al-LDHs adsorbent is prone to collapse. The elution rate of lithium ions of the Mg-LDHs-Cl adsorbent is 10% to 20% lower than that of the Li / Al-LDHs adsorbent, proving that its structure is more stable and the binding force between ions is higher, thus proving that the adsorption capacity of the Mg-LDHs-Cl adsorbent after elution is higher than that of the Li / Al-LDHs adsorbent.
[0066] Example 2
[0067] Example 2 provides an aluminum-based adsorbent of an aluminum-magnesium solid solution. The precursor of the aluminum-based adsorbent of an aluminum-magnesium solid solution in Example 2 is the same as that in Example 1.
[0068] 0.5 g of the adsorbent precursor of aluminum-magnesium solid solution was mixed with 50 ml, 100 ml, 150 ml, 200 ml and 250 ml of deionized water respectively, and the mixture was shaken and deintercalated on a constant temperature shaker at 40° C. for 2 h, and its XRD was tested.
[0069] Figure 3 For the XRD spectrum of the adsorbent in Example 2 provided by the present invention, refer to Figure 3 The prepared Mg-LDHs-Cl aluminum-based adsorbent did not show the peak corresponding to gibbsite when desorbed under different liquid-to-solid ratios, proving that the structure of the Mg-LDHs-Cl aluminum-based adsorbent remains basically stable under high-intensity elution conditions.
[0070] Example 3
[0071] Example 3 provides an aluminum-based adsorbent of an aluminum-magnesium solid solution. The precursor of the aluminum-based adsorbent of an aluminum-magnesium solid solution in Example 3 is the same as that in Example 1.
[0072] Take 0.5g of the adsorbent precursor of the aluminum-magnesium solid solution and mix them with 50ml, 100ml, 150ml, 200ml and 250ml of deionized water respectively, shake and deintercalate on a constant temperature shaker at 40℃ for 2h, take the upper clear liquid, and determine the amount of lithium ions eluted from the adsorbent precursor of the aluminum-magnesium solid solution in the desorption stage. Adsorb the obtained lower layer of the aluminum-magnesium solid solution adsorbent in a solution with a certain initial concentration of lithium ions, and then take the upper clear liquid in the adsorption stage to determine the adsorption capacity of the adsorbent of the aluminum-magnesium solid solution.
[0073] Figure 4 For the XRD spectrum of the adsorbent in Example 3 provided by the present invention, refer to Figure 4 In Example 3, the desorption amount of the Mg-LDHs-Cl aluminum-based adsorbent is: the first elution amount + the elution amount in the desorption stage, so the adsorption capacity will be smaller than the desorption amount.
[0074] See also Figure 4 In Example 3, the desorption amount of the Mg-LDHs-Cl aluminum-based adsorbent is about 18 mg / g, the first elution amount is about 13 mg / g, and the elution amount in the desorption stage is about 5 mg / g. The adsorption capacity in the desorption stage is more than 5 mg / g, so the elution amount in the normal desorption stage is less than or equal to the adsorption capacity.
[0075] See also Figure 4 , Li desorbed by Mg-LDHs-Cl aluminum adsorbent at different liquid-to-solid ratios + The capacity is almost stable, indicating that the enhancement of desorption intensity does not lead to the Li + Excessive desorption of ions causes the adsorbent structure to collapse. Figure 4 It can also be seen that the adsorption capacity of Mg-LDHs-Cl aluminum-based adsorbent is optimal under the liquid-to-solid ratio of 200.
[0076] In summary, the preparation method of an aluminum-based adsorbent of an aluminum-magnesium solid solution provided by the present invention does not require a complex reaction device and complex reaction condition control, and only requires that the prepared alkali solution be dripped into a mixed solution of a soluble aluminum salt, a lithium salt and a soluble magnesium salt at a certain flow rate, and then the precursor of the adsorbent is obtained by drying after solid-liquid separation by controlling the reaction temperature, reaction time, aging temperature, aging time and pH value. It can generate more active sites for lithium ions, improve the adsorption capacity and cycle stability of aluminum-based adsorbent materials, and achieve a high lithium embedding rate. The lithium content per gram of precursor is greater than 20 mg, the lithium embedding rate is generally greater than 70%, and the pure water elution rate of lithium ions is greater than 50%.
[0077] The above is only a specific implementation of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. A method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution, characterized in that: The preparation method comprises the following steps: S1, dissolving a soluble aluminum salt, a soluble lithium salt and a soluble magnesium salt in deionized water to obtain a mixed salt solution; S2, dissolving a soluble alkali in deionized water to obtain an alkali solution; S3, adding the alkaline solution dropwise to the mixed salt solution, and adjusting the pH value of the mixed salt solution to prepare a mixture; S4. Performing solid-liquid separation on the mixture to obtain a supernatant and a solid, and washing and drying the solid to obtain an aluminum-based adsorbent precursor powder.
2. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: In step S1, the soluble magnesium salt is selected from one or both of anhydrous magnesium chloride and hydrated magnesium chloride.
3. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: In step S1, the soluble aluminum salt is selected from one or more of anhydrous aluminum chloride, hydrated aluminum chloride, aluminum sulfate, hydrated aluminum sulfate, aluminum nitrate, hydrated aluminum nitrate, aluminum silicate and aluminum sulfide.
4. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: In step S1, the soluble lithium salt is selected from one or more of anhydrous lithium chloride, hydrated lithium chloride, anhydrous lithium hydroxide, hydrated lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate.
5. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: In step S1, the soluble alkali is selected from one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, ammonia water and urea.
6. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: In the step S1, the molar ratio of aluminum ions in the soluble aluminum salt, lithium ions in the soluble lithium salt and magnesium ions in the soluble magnesium salt is (0.1-1): (0.1-2): (0.1-2).
7. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: The mixed salt solution in step S1 has an aluminum ion concentration of 0.1 mol / L to 10 mol / L, a lithium ion concentration of 0.1 mol / L to 10 mol / L, and a magnesium ion concentration of 0.1 mol / L to 10 mol / L.
8. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: The concentration of the alkaline solution in step S2 is 0.5 mol / L to 5.0 mol / L.
9. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: In step S3, the alkaline solution is dripped at 35°C to 50°C at a rate of 5 mL / min. -1 ~60mL·min -1 The mixed salt solution is dripped into the mixed salt solution at a speed, and the pH value of the mixed salt solution is adjusted to 6.0-8.
0.
10. The method for preparing an aluminum-based adsorbent of an aluminum-magnesium solid solution according to claim 1, characterized in that: The temperature for drying the solid obtained in step S4 is 40°C to 80°C.